2020
DOI: 10.1200/jco.19.03316
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Radiation Dose Escalation in Patients With High-Risk Neuroblastoma and Gross Residual Disease After Surgery: A Report From the Children’s Oncology Group ANBL0532 Study

Abstract: PURPOSE A primary objective of the Children’s Oncology Group (COG) ANBL0532 phase III study was to assess the effect of increasing local dose of radiation to a residual primary tumor on the cumulative incidence of local progression (CILP) in patients with high-risk neuroblastoma. PATIENTS AND METHODS Newly diagnosed patients with high-risk neuroblastoma were randomly assigned or assigned to receive single or tandem autologous stem-cell transplantation (SCT) after induction chemotherapy. Local control consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Our study complements the existing literature on children undergoing RT for NB confirming high LC and acceptable OS. Local control and survival rates were similar to other studies, which demonstrated a 3-to 5-year LC and OS of 64.7-97% and 35-94% (13,(19)(20)(21)(22)(23)(24)(25)(26)(27). In the literature, the most common late effects associated with RT were musculoskeletal abnormalities, gastrointestinal dysfunctions, metabolic disorders, vascular changes, and secondary malignancies (22,(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 84%
“…Our study complements the existing literature on children undergoing RT for NB confirming high LC and acceptable OS. Local control and survival rates were similar to other studies, which demonstrated a 3-to 5-year LC and OS of 64.7-97% and 35-94% (13,(19)(20)(21)(22)(23)(24)(25)(26)(27). In the literature, the most common late effects associated with RT were musculoskeletal abnormalities, gastrointestinal dysfunctions, metabolic disorders, vascular changes, and secondary malignancies (22,(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 84%
“…With response-adjusted chemotherapy and resection, intermediate-risk patients have excellent survival rates of >90% at 5-years ( 3 , 5 , 12 , 13 ). Approximately 40–50% of patients are diagnosed with high-risk disease, which requires multimodality treatment, including chemotherapy, surgery, myeloablative chemotherapy with autologous stem cell transplant, radiation therapy, and anti-disialoganglioside (GD2)-based immunotherapy ( 10 , 14 17 ). For patients with high-risk disease, 5-year OS remains ~50% despite these aggressive strategies ( 8 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…At MSK, a radiotherapy dose of 2100 cGy is used for the prevention of soft tissue relapse at the primary site and at sites of bulky (>3 cm diameter) disease 20,21 . Although the optimal dose for radiotherapy of measurable disease has not been determined for the treatment of persistent MIBG‐avid skeletal metastases after completion of induction therapy or at recurrence, a dose of 3000‐3600 cGy is typically used 22,23 . Other investigators have also reported on the benefit of radiotherapy to metastatic sites at relapse 24 .…”
Section: Discussionmentioning
confidence: 99%